Accurate, rapid and reliable, fully automated MRI brainstem segmentation for application in multiple sclerosis and neurodegenerative diseases. Issue 14 (17th June 2019) - Sander, Laura; Pezold, Simon; Andermatt, Simon; Amann, Michael; Meier, Dominik; Wendebourg, Maria J.; Sinnecker, Tim; Radue, Ernst‐Wilhelm; Naegelin, Yvonne; Granziera, Cristina; Kappos, Ludwig; Wuerfel, Jens; et al.
Abstract: Neurodegenerative disorders, such as Alzheimer's disease (AD) and progressive forms of multiple sclerosis (MS), can affect the brainstem and are associated with atrophy that can be visualized by MRI. Anatomically accurate, large‐scale assessments of brainstem atrophy are challenging due to lack of automated, accurate segmentation methods. We present a novel method for brainstem volumetry using a fully‐automated segmentation approach based on multi‐dimensional gated recurrent units (MD‐GRU), a deep learning based semantic segmentation approach employing a convolutional adaptation of gated recurrent units. The neural network was trained on 67 3D‐high resolution T1‐weighted MRI scans from MS patients and healthy controls (HC) and refined using segmentations of 20 independent MS patients' scans. Reproducibility was assessed in MR test–retest experiments in 33 HC. Accuracy and robustness were examined by Dice scores comparing MD‐GRU to FreeSurfer and manual brainstem segmentations in independent MS and AD datasets. The mean %‐change/ SD between test–retest brainstem volumes were 0.45%/0.005 (MD‐GRU), 0.95%/0.009 (FreeSurfer), 0.86%/0.007 (manually edited segmentations). Comparing MD‐GRU to manually edited segmentations the mean Dice scores/ SD were: 0.97/0.005 (brainstem), 0.95/0.013 (mesencephalon), 0.98/0.006 (pons), 0.95/0.015 (medulla oblongata). Compared to the manual gold standard, MD‐GRU brainstem segmentations were more accurate than FreeSurfer segmentations ( p < .001). In the multi‐centric acquired AD data, the mean Dice score/ SD for the MD‐GRU‐manual segmentation comparison was 0.97/0.006. The fully automated brainstem segmentation method MD‐GRU provides accurate, highly reproducible, and robust segmentations in HC and patients with MS and AD in 200 s/scan on an Nvidia GeForce GTX 1080 GPU and shows potential for application in large and longitudinal datasets.